Depression as a major symptom of multiple sclerosis. - Whitlock, F A (1980)
Thirty patients suffering from multiple sclerosis have been compared with 30 patients suffering from other chronic neurological diseases. The degree of disability was similar in these two groups. The patients with multiple sclerosis had experienced more episodes of severe depression both before and after the onset of neurological symptoms. The possible reasons for these episodes are discussed and it is concluded that in some patients serious affective disorder may be a presenting or complicating feature of multiple sclerosis.